MEETING CUSTOMERS’ EXPECTATIONS IN SERVICE DELIVERY RELATED TO QUICK SERVICE RESTAURANTS IN INDONESIA - Sandika, Anggi; Hermina, Nurul; Abd Razak, Anis (International Journal of Psychosocial Rehabilitation, 2020)
This study is about the factors that contributes to customer satisfaction in the quick service restaurants in Indonesia. There is a growing competition in the industry as more and more new competitors enter the market. As the results rivalry among competitor is increased and provide a tough situation to win over the customer choices and business growth. This study used a self-administered questionnaire that was designed based on the research objectives and questions. Questionnaire were used to collect primary data. Final questionnaire consists of 25 items and divided into 5 parts. Part 1 is about the respondent profiles, part 2 is about the overall satisfaction. Part 3 to 5 is about the service quality, food quality and ambiance. All items were adapted from selected past research. 700 questionnaires were distributed through 50 selected quick service restaurants over all major cities in Indonesia. Out of 700 only 511were returns. It was found later that only 465 were good and usable for the data analysis. The results indicate that all three main factors are significantly influence customer satisfaction. It is about time for the industry players to be more alerts of customer needs and wants. Service provider need to be more advanced in understanding customer latent needs by applying market sensing. Overall, service provider has not much choices in accommodating the customer preferences as that is part of the requirement’s in order to sustain in the industry.